KAJIAN TEKNIK MENGGAMBAR WAYANG BEBER GAYA PACITAN JOKO SRI YONO - Gozali, Amir; Sutriyanto, S., (Acintya, 2015)
Wayang beber is one of the local heritage arts genius of our ancestors were awarded UN World Board through the (United Nations Educational, Scientific and Cultural Organization) UNESCO. Wayang beber consists of two styles of Pacitan style and Wonosari style. Both have a very clear distinction, which is present in the background and some of the characters involved. This study aimedto Pacitan style wayang beber, which is characterized by a very complicated background and has a very interesting artistic value. From both also have different kaedah manufacture especially when applying the colors used. This study examined the anatomy contained in wayang beber body, be it amain character or some other supporting cast. Anatomy directed against members of the body are found in various types of puppets such as eyes, nose, mouth, ears, hands, feet up clothes and accessories that are used. In addition, this study will reveal some of the symbols contained in the background, where the background can be seen from the condition and location that is happening ineach scene. In this study, the object is wayang beber with emphasis minitik studies on aspects of its art techniques and media that manufacture Pacitan style wayang beber Sri Yono Joko work. To solve some of the issues raised using a direct approach to the puppeteers, craftsmen and artists were stillprimarily Joko Sri Yono as an artist who holds the grip wayang beber style Pacitan, as well as the review of existing literature and using some of the theoretical approaches in the hope to replied the existing formula.Keywords: Wayang Beber, Style, Pacitan.